The Role of Financial Inclusion in Enhancing the Quality of Electronic Banking Services in Sudanese Banks (Field study on Bank of Khartoum) - Elseed, Abdelsalam Awad Khair; Mohammed, Asim Hassan (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to clarify the relationship between financial inclusion and electronic banking services quality, to recognize the extent of Sudanese bank interest in the quality of services provided to customers. The study adopted the descriptive analytical approach, historical approach, and the questionnaire used to collect data from Bank of Khartoum and analyzed it using statistical analysis program SPSS. The study found several results, the most important of which are; financial inclusion enhances quality of ATM’s service spread over a wide geographical area internally, financial inclusion enhances telephone banking service quality that banks provides to its customers, and financial inclusion enhances customers’ access to electronic banking service easily. The study recommended work to increase the awareness of Sudanese banks’ customers of the concept of financial inclusion and its role in enhancing electronic banking services’ quality through seminars and different advertisements.
Keywords: Financial inclusion; electronic banking services’ quality; Sudanese banks